Comment faire Peuple ? Le cas des protestations publiques au Maghreb - Smaïn Laarcher; Cédric Terzi (L’Année du Maghreb)
Reporting on the activities of cyber activists leads to investigating public protests and the many places where they are expressed. Cyber activism is not an autonomous sphere of activity. Rather, it is part of a larger movement to develop public issues. In other words, we are not in the presence of two distinct spheres : the sphere of cyber activists, a “virtual community” and that of society, a terrain for political struggles between groups whose interests are both different and contradictory. Under these circumstances, a comparative study reveals how communication tools, though technically identical, may serve different social and political purposes. Their use is primarily part of restraining national frameworks that give them form, consistency and symbolic meaning. While there is a link between cyberactivist militancy and popular protests in the three Maghreb countries, it is no less true that the connection between these worlds of organized protests unfolds differently depending on their national histories, balance of powers and extent of claims. Yet comparison is useful in revealing a central invariant element : the difficulty in acting as one people and collectively produce unity to institutionalize division ; in other words, to give their right and legitimacy to misunderstandings and politics. This is indeed a major challenge facing the three Maghreb countries today, through multiple public protests (whether riots or not).